Root separation modulates AMF diversity and composition in tomato–potato onion intercropping systems - Ibrahim, Musawar; Ullah, Asad; Pan, Xinjie; Lu, Jianzeng; Ibrahim, Musaddiq; Cao, Kunpeng; Liu, Shouwei; Zhou, Xingang; Wu, Fengzhi; Gao, Danmei (Frontiers in Microbiology, 2025)
Plant-plant interactions shape arbuscular mycorrhizal fungi (AMF) communities in rhizosphere soil, with tomato/potato-onion intercropping emerging as a promising agro-ecological strategy to optimize resource utilization. However, the role of root separation methods in modulating AMF diversity within intercropping systems remains unclear. Specifically, whether the AMF community in the rhizosphere of tomato and potato-onion intercropping differs from monoculture and how root separation methods modulate these effects. This study evaluates the effects of various root separation methods (no separation, 0.45 μm nylon membrane, 38 μm nylon membrane, and solid separation) on AMF diversity and composition in tomato/potato-onion intercropping and monoculture systems. High-throughput Illumina MiSeq sequencing was used to assess AMF diversity indices (Ace, Chao1, Shannon, and Simpson), and Principal Coordinate Analysis evaluated community structure. Results showed that the non-separation mode achieved the highest Ace and Chao1 indices, indicating greater richness, while intercropping lowered Shannon and Simpson indices. Intercropping significantly reduced Glomerales but increased Paraglomerales, under the non-separation mode. Similarly, it decreased Glomus while increasing Paraglomus in the rhizosphere of both crops. Principal Coordinate Analysis revealed that root separation distinctly altered AMF community structure, reflecting specific barrier effects on AMF interactions. Intercropping increased AMF abundance in the tomato rhizosphere but reduced it in potato-onion as shown by 18S rRNA gene abundance. These findings emphasize that minimizing root separation in intercropping enhances AMF diversity and functionality, providing valuable insights for sustainable agricultural management. Understanding the role of root interactions in shaping AMF communities can help optimizing intercropping strategies to improve soil health and nutrient dynamics.